A tale of social Q&As in the united states and china. Issue 1 (2014) - Zhang, Yin; Deng, Shengli; Yang, Lina
ABSTRACT: This poster reports a study that examines and compares how Social Questions and Answers (Social Q&As, or SQAs) are used in the United States and China. The data were collected from users of the most popular SQA site in the two countries respectively. The preliminary findings show that overall SQA serves various user needs, and user satisfaction is at about 70% for both sites. However, user satisfaction with SQA answers varies by the types of questions. This is particularly relevant for Yahoo! Answers users in the United States. SQA users in both countries point out a common set of the most important factors as well as the least important factors for a virtual information service. The practical implications of the study are discussed.